Pengaruh Ukuran Perusahaan dan Umur Perusahaan Terhadap Tax Avoidance pada Sektor Pertambangan di BEI - Firmansyah Firmansyah (Economics, Business and Management Science Journal, 2021)
The purpose of this study was to determine the effect of company size on tax avoidance in mining companies on the IDX, to determine the effect of company age on tax avoidance in mining companies on the IDX, and to determine the effect of company size and company age on tax avoidance in mining companies on the IDX. The results of this study are the size of the company, and the age of the company affect tax avoidance either partially or simultaneously